Harvesting Techniques in Traditional Shrimp Culture - p., Pravin; K., Ravindran (Fishery Technology, 2025)
Harvesting techniques in traditional shrimp culture are diverse and varied depending upon the requirements of each area. The design, the technical details and operational features of the different harvesting methods prevalent in the traditional shrimp culture in Kerala coast have been studied and described in this paper